2014
DOI: 10.1111/aogs.12449
|View full text |Cite
|
Sign up to set email alerts
|

Term breech deliveries in the Netherlands: did the increased cesarean rate affect neonatal outcome? A population‐based cohort study

Abstract: Adjustment of the national guidelines after publication of the Term Breech Trial resulted in a shift towards elective cesarean and a decrease of perinatal mortality and morbidity among women delivering a child in breech at term. Still, 40% of these women attempt vaginal birth. The relative safety of an elective cesarean should be weighed against the consequences of a scarred uterus in future pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 24 publications
6
94
3
2
Order By: Relevance
“…The same correlation was also observed in a Dutch study [35]. Both the French and the Dutch studies registered a slight decrease in the rate of C-sections for breech presentation after 2005 [34,35]. This could be due to a follow-up study by Whyte et al which found no difference with regard to death or neurological developmental delay between children in breech presentation delivered vaginally or by C-section by the time the children were two years old [36].…”
Section: Risk Factors For C-sectionsupporting
confidence: 70%
See 1 more Smart Citation
“…The same correlation was also observed in a Dutch study [35]. Both the French and the Dutch studies registered a slight decrease in the rate of C-sections for breech presentation after 2005 [34,35]. This could be due to a follow-up study by Whyte et al which found no difference with regard to death or neurological developmental delay between children in breech presentation delivered vaginally or by C-section by the time the children were two years old [36].…”
Section: Risk Factors For C-sectionsupporting
confidence: 70%
“…A study of French perinatal data (from 1994 to 2010) showed a significant increase in C-section rates for breech presentation following the publication of that study [34]. The same correlation was also observed in a Dutch study [35]. Both the French and the Dutch studies registered a slight decrease in the rate of C-sections for breech presentation after 2005 [34,35].…”
Section: Risk Factors For C-sectionmentioning
confidence: 61%
“…Studies 2,3,4,29,30,31 have reported better neonatal morbidity in the form of low apgar scores, neonatal intensive care admissions, birth trauma in breech born by elective caesarean section and recommend caesarean section for breech. On the contrary, several authors have reported good neonatal outcomes win patients undergoing vaginal breech birth.…”
Section: Discussionmentioning
confidence: 99%
“…Our success rate for attempted vaginal birth was 57.5%, somewhat lower than that in the PREMODA study (71%) and similar to that in the Dutch cohort (≈50%). 10,21 A vaginal breech delivery entails short-term fetal distress and this is reflected in the early perinatal parameters. Indeed, the overall results at this stage are better for PCS than for PVD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as in other published series, more than 97% of infants from PVDs progressed well without the need for extra neonatal care. 10,21 We had one case of intrapartum death, the baby dying in the birth canal secondary to complications during assisted vaginal delivery, producing a mortality rate of 1.1‰ (1/891) in the PVD group. This rate is lower than in the overall results presented in the Term Breech Trial (12.5‰ (13/1039)) and in the subgroup of countries with low perinatal mortality rates (5.8‰ (3/511)), 1 vaginal breech deliveries (0.8‰ (2/2502) 10 and 1.6‰ (30/18 388) 21 ).…”
Section: Discussionmentioning
confidence: 99%